Sources of Operating Costs - Mackie, Peter (World Bank, Washington, DC, 2012)
Historically, road vehicle operating costs have tended to dominate highway economic appraisals in developing countries, due to the poor road surfaces that can occur there. The operating costs of railways and ports are also substantial, and form key components of cost benefit analyses of their associated infrastructure. The definition of operating costs for Bank projects is therefore important in obtaining a reliable economic appraisal. In this Note, Section 1 introduces the key issues associated with operating costs, whilst the following sections discuss the components and sources of operating costs by mode. Road vehicle operating costs are presented in Section 2, railway operating costs in Section 3, and port operating costs in Section 4.